Acquired renal glucosuria in an undifferentiated connective tissue disease patient with a SLC5A2 heterozygous mutation: A case report - Gu, Xiangchen (Medicine (Baltimore), 2018)
INTRODUCTION: Renal glucosuria is a renal tubular disorder caused by genetic conditions, drugs, and poisons. Mutations in the SLC5A2 gene are recently found to be responsible for the inherited renal glucosuria, while undifferentiated connective tissue disease (UCTD) was not considered pathogenic for renal glucosuria. Here, we present a case of acquired renal glucosuria in a UCTD patient. PATIENT CONCERNS: A 30-year-old woman was seen in the outpatient clinic for complaints of frequent urination and dysuria. Laboratory tests showed a urinary tract infection (UTI) and persistent renal glucosuria. After antibiotic treatment, the UTI symptoms were relieved, but the renal glucosuria remained. DIAGNOSIS: Laboratory tests ruled out renal tubular acidosis and diabetes mellitus. Genetic analysis showed a heterozygous mutations in the SLC5A2 gene. Meanwhile, immunological tests showed a high antinuclear antibody titer (1:160) and an elevated anti-Rho/SSA antibody level. Schirmer test, tear breakup time, and lip biopsy results were all negative. The patient did not meet the criteria for any known connective diseases. Therefore, she was diagnosed with UCTD. Interventions: The patient was started with the treatment of Hydroxychloroquine. OUTCOMES: Hydroxychloroquine treatment resolved the renal glucosuria. The patient's follow- up urinalysis showed no glucosuria at all. LESSONS: This is the first case report to demonstrate that UCTD may induce renal glucosuria in a patient with a heterozygous mutation in SLC5A2. This case suggests that during the process of diagnosing renal glucosuria, in addition to familial renal glucosuria (FRG), autoimmune diseases, though rare, should also be taken into consideration.